Professional Quality of Life among Oncology Nurses at Turkish Palestinian Friendship Hospital in Gaza Strip - Tareq Khattab; Yousef Aljeesh (Nursing and Health Sciences Journal (NHSJ), 2022)
Purpose: Study was conducted to identify the positive and negative aspects of professional quality of life among nurses at the Turkish Palestinian Friendship Hospital in Gaza Strip, as well as to look into the relationship between sociodemographic factors and professional quality of life among nurses at the Turkish Palestinian Friendship Hospital in Gaza Strip. Method: A descriptive cross-sectional design. The Professional Quality of Life Scale (ProQoL), version 5, was used to collect data from 74 nurses who participated in the study, with an 84% response rate. Results: Study participants had high levels of compassion satisfaction (M= 3.9068; SD= 0.86979; WM 78.1%), moderate level of burnout (M= 3.2784; SD= 0.60845; WM 65.5%), and moderate level of secondary traumatic stress (M= 3.0027; SD= 0.77211; WM 60%). There are statistically significant determinants for compassion satisfaction with age group up to 40 years and older (F= 3.406, P= 0.039), participants who received oncology education (T = 2.297, P= 0.025). Also, there is a significant relationship between age group "31-40 years" and secondary traumatic stress in comparison with other groups (F= 4.234, P= 0.018). There are statistically significant determinants for secondary traumatic stress with moderate level of income (F= 6.057, P= 0.004). Also, there is a significant relationship between moderate level of income and burnout (F= 7.497, P= 0.001). Conclusions: Compassion satisfaction is high but burnout and secondary traumatic stress are moderate. Hospital administrators should work on developing strategies to improve compassion satisfaction while reducing burnout and secondary traumatic stress.